Little Ice Age history of Tzeetsaytsul Glacier, Tweedsmuir Provincial Park, British Columbia - Smith, Dan; Desloges, Joseph (Géographie physique et Quaternaire, 2000)
Abstract This paper describes licheno- metric and dendroglaciological investigations of Little Ice Age (LIA) deposits at Tzeetsaytsul Glacier, Tweedsmuir Provincial Park, British Columbia. The glacier originates from an ice- field on the northeast flank of Tzeetsaytsul Peak and terminates in a moraine-dammed lake. A stream draining the lake has incised the moraine dam and flows through nested moraines into a second lake. Two end moraines near the lower lake record separate advances, with numerous morainic ridges found between the two lakes. A locally calibrated Rhizocarpon geographicum growth curve was constructed and provides relative ages for all the moraines. Absolute dates from wood fragments collected from within the morainic debris were determined by matching their annual growth ring patterns to a local Abies lasiocarpa tree-ring chronology. The outermost terminal moraine was deposited by a 17th century advance that culminated in ca. 1700. Following subsequent recession, Tzeetsaytsul Glacier readvanced to build a second terminal moraine by the mid-1800s. Recession of this glacier occurred within 40 years and by 1935 the glacier was beginning to calve into the uppermost lake. The research shows that the most recent LIA advance of Tzeetsaytsul Glacier was not the most extensive, and that multiple events characterized the late-LIA. Application of the Rhizocarpon growth curve indicates a previously unreported 17th century advance at other glaciers in the region. These findings serve to reinforce the synchroneity of late-LIA glacier fluctuations within the coastal cordillera of NW North America suggesting that they record regional climate forcing.